Pengembangan Sungai Sembra Sebagai Objek Wisata di Kampung Srer Distrik Serumuk Kabupaten Sorong Selatan - Kehek, Linda Yulce; Andaria, Kalvin Salindeho; Lobja, Xaverius Erick; Rewah, Fonny (Fakultas Ilmu Sosial dan Hukum, 2024)
The research focused on developing the Sembra River tourist attraction in Srer Village, South Sorong Regency. The Sembra River is a natural tourist attraction with clear and clean water that is bluish in color and lush trees that provide comfort and tranquility for tourists. To develop this attraction, public facilities such as supporting transportation, souvenirs, food, snacks, accommodation, and security are being developed. Community involvement is also important. Collaboration between the regional rights community and the government was built to improve the community's mindset and carry out the promotion of the Sembra River Tourism Object. Promotion is carried out through global social media, local government websites, and direct outreach to the community and regional guests to attract tourists.